2013
DOI: 10.1155/2013/714168
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Three-Dimensional Hinge Moment Characteristics Generated by the ONERA-M6 Wing with an Aileron

Abstract: The hinge moment characteristics for ONERA-M6 wing with aileron configuration have been investigated numerically based on the different gaps and deflecting angles. The results show that the effects on the wing made by the deflecting aileron are notable. Comparing with the nonaileron case, the chordwise pressure coefficient distribution for the wing with aileron has shown the totally different trends. The small gap can force the air flow through and form the extremely strong spraying flow. It can directly destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Characteristics for the zero angle of attack were determined, but for other angles of attack, the change in hinge moment is similar for particular configurations. As the deflecting angle increases, the hinge moments decrease (Zhang et al , 2013). It can be noted that the change in the hinge moment of the system is not dependent on the presence of an aileron slat in a non-sealed configuration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics for the zero angle of attack were determined, but for other angles of attack, the change in hinge moment is similar for particular configurations. As the deflecting angle increases, the hinge moments decrease (Zhang et al , 2013). It can be noted that the change in the hinge moment of the system is not dependent on the presence of an aileron slat in a non-sealed configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, with the increase of the aileron area and the airspeed, the respective hinge moment can grow up. To complete the deflecting motion of the aileron by means of the control stick, more operating force will be needed (Zhang et al , 2013). To determine the characteristics of the hinge moment, it is necessary to specify the pressure distributions on the control surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Gaya counter tersebut adalah hinge moment, yang berupa restoring tendency dan floating tendency pada komponen control [1]. Menurut penelitian yang dilakukan oleh yang dilakukan oleh Zhang diketahui jika perubahan pada geometri rudder dapat berpengaruh pada hasil Ch yang dihasilkan oleh rudder [2]. Perubahan geometri dapat berubah dengan cara merubah desain rudder dan memberikan sudut defleksi pada rudder.…”
Section: Pendahuluanunclassified
“…G.Q. Zhang et al studied the effect of wing angle of attack on aileron hinge moments, and the results showed that under small clearances, hinge moments decreased gradually with the increase of angle of attack [30].…”
Section: Introductionmentioning
confidence: 99%